Chorology of the Asteraceae of Coahuila, Mexico - Villarreal Quintanilla, Jose Angel; Valdes Reyna, Jesus; Villaseñor R., Jose Luis (Instituto de Ecología, A.C., 1996)
A study was conducted to establish the distribution patterns of the Asteraceae in the state of Coahuila, México. Therefore, a list of species was compiled, and their distribution determined. The Asteraceae family is dominated in Coahuila by species of the tribe Heliantheae followed by the Astereae and Eupatorieae. The flora has an important regional component. Most of the taxa have their distribution limited to México, followed by those distributed in North America and those limited to the Chihuahuan Desert region.